Electroactive ZnO: Mechanisms, Conductivity, and Advances in Zn Alkaline Battery Cycling. Issue 15 (23rd February 2022) - Hawkins, Brendan E.; Turney, Damon E.; Messinger, Robert J.; Kiss, Andrew M.; Yadav, Gautam G.; Banerjee, Sanjoy; Lambert, Timothy N.
Abstract: Zinc oxide is of great interest for advanced energy devices because of its low cost, wide direct bandgap, non‐toxicity, and facile electrochemistry. In zinc alkaline batteries, ZnO plays a critical role in electrode passivation, a process that hinders commercialization and remains poorly understood. Here, novel observations of an electroactive type of ZnO formed in Zn‐metal alkaline electrodes are disclosed. The electrical conductivity of battery‐formed ZnO is measured and found to vary by factors of up to 10 4, which provides a first‐principles‐based understanding of Zn passivation in industrial alkaline batteries. Simultaneous with this conductivity change, protons are inserted into the crystal structure and electrons are inserted into the conduction band in quantities up to ≈10 20 cm −3 and ≈1 mAh gZnO −1 . Electron insertion causes blue electrochromic coloration with efficiencies and rates competitive with leading electrochromic materials. The electroactivity of ZnO is evidently enabled by rapid crystal growth, which forms defects that complex with inserted cations, charge‐balanced by the increase of conduction band electrons. This property distinguishes electroactive ZnO from inactive classical ZnO. Knowledge of this phenomenon is applied to improve cycling performance of industrial‐design electrodes at 50% zinc utilization and the authors propose other uses for ZnO such as electrochromic devices. Abstract : The mechanisms enabling the electroactivity of ZnO in zinc alkaline batteries are elucidated. Rapid ZnO crystal growth promotes the formation of defects that complex with cations inserted from the electrolyte. Co‐insertion of conduction band electrons increases ZnO conductivity, which varies as a function of potential. This phenomenon explains zinc electrode passivation and informs control tactics for improved battery performance.